POSTPARTUM DEPRESSION: ASSESSMENT OF CULTURAL RISK FACTORS - Amina Hanif Tarar (Army Medical College Rawalpindi, 2021)
Objective: To explore the cultural risk factors influencing the Postpartum Depression of first-born infants’ mothers.